Гарантії кримінального процесу - Слінько, С. В.; Slinko, S. V.; Максимова, Л. О.; Maksymova, L. O. (Право.ua. - 2024. - № 1. - С. 59-64, 2024)
Надано теоретичне визначення процесуальних гарантій у кримінальному процесі. Запропоновано визначення юридичних гарантій за фактом закріплення обставин кримінального правопорушення під час збирання, оцінки доказів, у разі проведення процесуальних, слідчих (розшукових) та судових дій. Приділяється увага забезпечення гарантій під час ознайомлення з матеріалами кримінального провадження на стадіях судового розгляду. Доведено обставини гарантії оскарження дій або бездіяльності слідчого, прокурора. Розкрито теоретичний та практичний зміст забезпечення гарантій сторони обвинувачення та сторони захисту. Звернена увага на процесуальні гарантії учасників, які забезпечують допомогу проведення досудового розслідування та судового розгляду.

The theoretical provisions of the criminal process include the institution of guarantees of rights and interests of its participants. The basis for ensuring guarantees in the criminal process are constitutional, legal, special principles that regulate the application of guarantees during criminal prosecution, and also ensure the protection of rights, freedoms and interests during pre-trial investigation and trial of criminal proceedings. The Criminal Procedure Law established guarantees for each participant in legal relations, which he must use during the pre-trial investigation and trial of criminal proceedings. It is proposed to define legal guarantees based on the fact of establishing the circumstances of a criminal offense during the collection and evaluation of evidence, in the case of procedural, investigative (search) and judicial actions. Attention is paid to ensuring guarantees during the review of the materials of the criminal proceedings at the stages of the trial. The circumstances of the guarantee of appeal against the actions or inaction of the investigator, prosecutor have been proven. The theoretical and practical content of ensuring the guarantees of the prosecution and the defense is revealed. Attention is paid to the procedural guarantees of the participants, which provide assistance in the conduct of pretrial investigation and trial. A theoretical definition of procedural guarantees in the criminal process is proposed.

Дано теоретическое определение процессуальных гарантий в уголовном процессе. Предложено определение юридических гарантий по факту закрепления обстоятельств уголовного правонарушения при сборе, оценке доказательств, в случае проведения процессуальных, следственных (розыскных) и судебных действий. Уделяется внимание обеспечению гарантий при ознакомлении с материалами уголовного производства на стадиях судебного разбирательства. Доказаны обстоятельства гарантии обжалования действий или бездействия следователя, прокурора. Раскрыто теоретическое и практическое содержание обеспечения гарантий стороны обвинения и защиты. Обращено внимание на процессуальные гарантии участников, обеспечивающих помощь в проведении досудебного расследования и судебного разбирательства.
Guarantees of the criminal process
Keywords: кримінальний процес; гарантії; статус; учасники; сторона обвинувачення; сторона захисту; досудове розслідування; слідчий; прокурор; суддя; criminal process; guarantees; status; participants; prosecution; defense; pre-trial investigation; investigator; prosecutor; judge; уголовный процесс; гарантии; участники; сторона обвинения; сторона защиты; досудебное расследование; следователь; судья